2020
DOI: 10.3390/plants9020236
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Infrared Drying on Color, Projected Area, Drying Time, and Total Phenolic Content of Rose (Rose electron) Petals

Abstract: The effects of different drying temperatures (50, 60, 70 °C) on the quality of rose (Rose electron) petals were evaluated in this study. Drying time decreased from 1680 s to 600 s with increased infrared temperature. The temperature and time were increased from 50 °C to 70 °C and 30 min to 60 min, respectively, and a decrease in the fruit color quality was observed. The projected area (PA) of rose petals was affected significantly from temperature. After the drying process, the largest PA was observed as 33.35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Fresh and dried sage samples were ground and methanol:water (20:80 v/v) solution was added to grounded sage samples with the ratio 1:50. This mixture was shaken for 2 h in a shaking incubator (Memmert WB-22) at room temperature [20]. After the extraction process, the solid/liquid mix was centrifuged (Hettich, Universal 320R, Tuttlingen, Germany) at 4,000 rpm for 10 min.…”
Section: Extraction Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh and dried sage samples were ground and methanol:water (20:80 v/v) solution was added to grounded sage samples with the ratio 1:50. This mixture was shaken for 2 h in a shaking incubator (Memmert WB-22) at room temperature [20]. After the extraction process, the solid/liquid mix was centrifuged (Hettich, Universal 320R, Tuttlingen, Germany) at 4,000 rpm for 10 min.…”
Section: Extraction Proceduresmentioning
confidence: 99%
“…They investigated that drying time and bioactive properties were strongly affected on drying conditions [19]. Jonas et al (2021) investigated the effect of oven drying conditions on the key aroma content of sage leaves [20]. However, there have been no studies on the effect of different infrared drying conditions on total bioactive content and individual phenolic components of sage leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have also reported a strong correlation between antioxidant activity and total polyphenol content, suggesting that phenolic compounds may be the main contributors to antioxidant capacity. Selvi et al (2020) reported the impact of infrared drying on total phenolic content of rose petals (rose electron). They demonstrated an increase in TPC with increasing temperatures of roses.…”
Section: Progress Of Processing Technologies Pre‐treatment Handling A...mentioning
confidence: 99%
“…Although microwave drying can shorten the drying time and keep the nutritional components, direct contact with microwave may lead to carbonization and tissue damage, and therefore the visual quality of dried flowers may be poor.Most studies of edible flowers have tested different drying methods and assessed their impact on the quality of flowers. Many studies have also reported a strong correlation between antioxidant activity and total polyphenol content, suggesting that phenolic compounds may be the main contributors to antioxidant capacity Selvi et al (2020). reported the impact of infrared drying on total phenolic content of rose petals (rose electron).…”
mentioning
confidence: 99%
“…During the drying process, the intrinsic quality characteristics (texture, flavor, aroma), sensory characteristics (color, shape, size) and nutritional value of fruit and vegetable products change [13,14]. These characteristics variations feature a very high consumer acceptance for commercial production.…”
Section: Introductionmentioning
confidence: 99%